Preventing occupational ailments and disorders associated with cassava mash dewatering techniques - Kolawole, P.; Agbetoye, L.A.S.; Ogunlowo, A.S.; Samuel, T.M. (Scientific and Academic Publishing, 2012)
Methods in use to reduce the cyanide level in cassava were found to be dangerous to the processors. To reduce occupational hazards, cassava processors sometimes wear protective coverings such as hand gloves, overall, mouth/nose hood, eye goggles which are not comfortable. Each of the steps in cassava processing stages exposes workers to various occupationally related ailments and disorders of ergonomic origin. The operators of dewatering tools are at the risks of suffering from different ailments.The traditional processors still depend on the old technique and resources. Workers are often exposed to cyanide and many are scared of the toxic effect of cassava juice. To prevent the occupational related ailment, mash process handling machine was developed and evaluated. The obtained result by use of the machine confirms the operators’ protection. The obtained mash cake was found to meet the stake holders’ requirement of 47-50% moisture content wet bases without human contact.